The preaching of the Mishpat of Isaiah 5:1-7 in the context of injustice in the middle belt region of Nigeria - Daniel, Nicodemus Pele (Stellenbosch : Stellenbosch University, 2014)
Thesis (MTh)--Stellenbosch University, 2014.